Respuesta :
Answer:
[tex]b=11, b=17[/tex]
Step-by-step explanation:
To get rid of the parenthesis, distribute:
[tex]b(28-b)=187,\\28b-b^2=187[/tex]
Move all terms to one side and factor:
[tex]b^2-28b+187=0,\\(b-11)(b-17)=0,\\\begin{cases}b-11=0,b=\boxed{11}\\b-17=0,b=\boxed{17}\end{cases}[/tex]
Answer:
b = 11, 17
Step-by-step explanation:
=> (28 - b) × b = 187
=> 28b - b² = 187
- subtracting 187 from both sides
=> 28b - b² - 187 = 0
- dividing the equation by (-1) and rearranging
=> b² - 28b + 187 = 0
- breaking -28b into 2 variables such that the variable multiply to form 187b²
=> b² - 11b- 17b + 187 = 0
{as (-11b)×(-17b) = 187b² and (-11b)+ (-17b) = -28b }
=> b (b - 11) - 17(b - 11) = 0
=> (b- 11)(b - 17) = 0
- either
(b - 11) = 0
=> b = 11
- or
(b - 17) = 0
=> b = 17
therfore,